Alliance of equals - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Lee, Sharon, 1952- Liaden universe., 2017)
After trying to maintain Clan Korval as a top trading clan, Master Trader Shan yos'Galan finds himself under attack by the DOI, while his apprentice, Padi yos'Galan, is keeping a secret about herself that could threaten her life.